2021
DOI: 10.1186/s40364-021-00310-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological trends of women’s cancers from 1990 to 2019 at the global, regional, and national levels: a population-based study

Abstract: Background Every year around the world, more than 2 million women are diagnosed with breast cancer and genital tract cancers. However, there are rare studies comprehensively describing the global and regional trends of incidence and mortality of women’s cancers. Methods To study the burden and trend of women’s cancers, we conducted this cross-sectional study based on the epidemiologic data of Global Burden of Disease 2019. In this study, female pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 45 publications
2
54
0
3
Order By: Relevance
“…Previous paper about the incidence and mortality burden of ovarian cancer confirmed our findings (23). Besides, the latest research about the global disease burden of women cancer revealed that the incidence, deaths, and DALYs of ovarian cancer were 294,420, 198,410, and 5,359,740, respectively in 2019 globally which showed increases from 2017 (24). These findings could be helpful to the allocation of the limited health service resources as well as the evaluation of interventions or programs.…”
Section: Discussionsupporting
confidence: 86%
“…Previous paper about the incidence and mortality burden of ovarian cancer confirmed our findings (23). Besides, the latest research about the global disease burden of women cancer revealed that the incidence, deaths, and DALYs of ovarian cancer were 294,420, 198,410, and 5,359,740, respectively in 2019 globally which showed increases from 2017 (24). These findings could be helpful to the allocation of the limited health service resources as well as the evaluation of interventions or programs.…”
Section: Discussionsupporting
confidence: 86%
“…Global Burden of Disease 2019 (GBD 2019) provided the information about the burdens of 369 diseases and injuries along with 87 risk factors in the globe, different geographic areas, and 204 countries and territories ( 15 , 16 ) and the detailed introduction was shown in Supplementary File 1 , which aimed at quantifying the relative magnitude of health loss due to risk factors, injuries and diseases by age, gender, SDI (sociodemographic index) and geographic location at a specific point in time. Data on infective endocarditis burden from 1990 to 2019 including its incidence, death, DALYs, and their corresponding age-standardized rates (ASRs), were acquired from the Global Health Data Exchange GBD Results Tool ( http://ghdx.healthdata.org/gbd-results-tool ) (date of data extraction, 21 April of 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Breast cancer mortality rates have been declining globally in the last three decades [ 1 ], principally owing to improvements in treatment and the early detection by mammography screening [ 2 , 3 ], while the number of breast cancer deaths and disability-adjusted life years (DALYs) have continued to increase [ 4 ], which perhaps can be attributed to the population growth and inadequacy of prevention strategies [ 2 ]. Keeping physically active is one of the most important recommendations presented by the World Cancer Research Fund, which suggests staying at least moderately physically active and limiting sedentary habits [ 5 ].…”
Section: Introductionmentioning
confidence: 99%